The New Zealand timber and flax trade, 1769-1840 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in History at Massey University - Wigglesworth, Roger Philip (Massey University, 1981)
This thesis is an examination of the commercial, social and political dimensions of the New Zealand timber and flax trade 1769-1840. Chapters One to Three provide a chronological account of the trade. The level of activity was sporadic until 1827 after which time the trade expanded. The years 1769-1827 were a period of familiarization. The Europeans needed to experiment wit the New Zealand products, to test the market for them and to settle traders at New Zealand. The Maoris had to learn what Europeans required and to adjust to the demands of trading. Each group used these years to get to know the other and to establish the rapport required for the trade to function. Exports of wood and fibre from New Zealand increased rapidly after 1827 because the Europeans were prepared to invest in them and the Maoris were willing to produce enough timber and flax to sustain an export trade. During the 1830s the trade prospered only for as long as the markets for the products were buoyant and the Maoris were prepared to continue to assist with the production of them. Timber and flax trading could substantially affect the lives of those involved in it. Chapters Four and Five examine how traders adapted to the demands of the New Zealand physical and social environment and how Maoris faced changes in their work and settlement patterns, health, inter-tribal relations, and material culture. Chapter Six discusses the increasing interest by British and colonial governments in New Zealand affairs which was stimulated in large part by the timber and flax trade. For example the sent naval vessels and issued contracts to private firms to collect cargoes of these products. They also sought to regulate affairs in New Zealand (by passing Acts of Parliament, by sending naval vessels to cruise the coast and by appointing a British Resident) at least partly in order to provide an environment whic would be conducive to trading. The eventual British decision to annex New Zealand was strongly influenced by the pressure exerted on the government by those who were interested in trading with that country.
Keywords: Lumber trade; Flax industry; Forests and forestry; Phormium tenax; Maori; Export trade